Measurement of Factors That Can Improve the Implementation of Accrual-Based Accounting in Regional Government Agencies - Kewo, Cecilia Lelly; Kewo, Stella Theodora (International Journal of Economics and Financial Issues, 2024)
Accruals provide financial information that is more relevant and reliable in financial reporting and decision-making. Therefore, this research aims to analyze the factors that influence the implementation of accrual accounting in government, namely financial regulatory factors, employee competence, and commitment to the organization. The primary data used was taken from 173 government agencies in Indonesia using random sampling, then the collected data was analyzed using structural equation modeling with a partial least squares approach with an alpha of 5%. The results show that financial regulations, employee competence, and commitment to the organization have a positive impact on the implementation of accrual accounting in government. This has significant implications for the government to increase the implementation of government accounting standards, increase employee competency through training and development related to accounting practices and knowledge, and increase commitment to the organization through developing an organizational culture that supports the implementation of accrual accounting in government.